Effects of melt superheat treatment on microstructure and wear behaviours of hypereutectic Al–20Si alloy. (July 2014) - Li, Q. L.; Xia, T. D.; Lan, Y. F.; Li, P. F.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, the effects of melt superheat treatment on the microstructural evolution and wear behaviours of hypereutectic Al–20Si alloy were investigated. The morphology of primary and eutectic Si phase was analysed by optical microscopy (OM) and scanning electron microscopy (SEM). The results of OM and SEM reveal that increasing the melt superheat temperature can significantly refine the primary and eutectic Si of hypereutectic Al–20Si alloy. The average size of primary Si was reduced from 94 to 47 μm, and its morphology was transformed from coarse and irregular shape to fine blocky shape or particles, while the eutectic Si was modified into fine fibrous structure. The differential scanning calorimeter curves show an exothermic reaction happens when the melt temperature arrives at 940·5°C, and the exothermic peak is at 951°C. Friction and wear tests show that the friction coefficient and specific wear rate of Al–20Si alloy gradually decrease with increasing melt superheat treatment temperature. In addition, the wear mechanism of hypereutectic Al–20Si alloy before and after refining the primary and eutectic Si phase was also discussed.